LYSIS AND DISSOLUTION OF CELLS AND ENVELOPES OF AN EXTREMELY HALOPHILIC BACTERIUM - Kushner, D. J. (1964)
Kushner, D. J. (National Research Council, Ottawa, Ontario, Canada). Lysis and dissolution of cells and envelopes of an extremely halophilic bacterium. J. Bacteriol. 87:1147–1156. 1964.—Envelopes of the extremely halophilic bacterium, Halobacterium cutirubrum, disintegrate in the absence of salt to form much smaller particles. Extensive proteolytic breakdown to compounds of low molecular weight is not involved in this process or in the lysis of cells in the absence of salt. NaCl is much more effective than KCl or NH(4)Cl in preserving the integrity of intact cells, but is only slightly more effective in preserving the integrity of mechanically prepared envelopes, of cells made permeable by treatment with acid, and of cells made permeable by formalin fixation followed by exposure to water. MgCl(2) is much more effective in preserving the integrity of these preparations than of intact cells. The results suggest that the exterior cell surface has sites specifically requiring Na(+) to maintain their integrity, whereas the interior surface has sites whose integrity is maintained at least as well by K(+) or NH(4)(+) as by Na(+).